Juridical Implications of "May Report" in Foreign Will Reporting by Indonesian - R.A Berliany Maudy Ratu Bendy; Amelia Sri Kusuma Dewi; Dyah Widhiawati (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2027)
This study aims to analyze the interpretation of the phrase "may report" in Article 10 of the Minister of Law Regulation No. 16 of 2025 concerning the Reporting of Wills and Applications for the Issuance of Certificates of Wills in relation to the reporting of wills made abroad by Indonesian citizens, as well as the juridical implications of failing to register such wills for the implementation of inheritance in Indonesia. This study employs a normative legal research method using statutory, conceptual, and analytical approaches, with legal analysis conducted through grammatical, systematic, historical, and teleological interpretation. The legal materials consist of primary legal sources, including the Indonesian Civil Code, the Minister of Law Regulation No. 16 of 2025, and other relevant legislation, supported by secondary legal materials in the form of books and scholarly journal articles. The research gap lies in the absence of studies that specifically examine the normative character of the phrase "may report" and its legal consequences for the implementation of inheritance law in Indonesia. The novelty of this study is the formulation of a normative construction arguing that the phrase constitutes an incomplete legal norm because it merely grants discretionary authority without prescribing the legal consequences of failing to report a will. The findings reveal that a will executed abroad remains legally valid under the principle of locus regit actum and the Indonesian Civil Code. However, the failure to report the will results in its exclusion from the Central Register of Wills, prevents its inclusion in the Certificate of Wills, diminishes the functions of legal publicity and traceability, and may consequently create legal uncertainty in the administration of inheritance. The principal contribution of this study is to provide a conceptual foundation for revising Article 10 by expressly regulating the legal consequences arising from the failure to report wills executed abroad.